Sistem Informasi Inventori Aset Berbasis Web Pada Harris Hotel Denpasar - I Nyoman Rikajaya; Made Liandana; Putu Pande Yudiastra (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2020)
Harris Hotel Denpasar is one of the 4-star hotels in Denpasar City which has a large value and number of assets, however the asset recording process is still conventionally using microsoft office excel software. This has become a problem that inflicted the burdensome to conduct the data search and distribute it to the related user. In this study, a web-based management information system is advanced using the waterfall model type of development system starting from the first stage namely the analysis stage and specification stage until the last stage namely the operation and maintenance stage. The system information is depicted using DFD (Data Flow Diagram) starting from the Flowmap of the designed system, Context Diagram, Data Flow Diagram Level 0 and Data Flow Diagram Level 1 along with the data base design using Entity Relationship Diagram (ERD). Web-based information system of the asset inventory in Harris Hotel Denpasar is implemented using the PHP native programming language, MySQL database and template Framework Bootstrap. It has the asset inventory of data management features, including data replenishments, data updates, listing of damaged goods, recording log activities, print reports and view the statistics. The assessment of the web-based information system of the asset inventory in Harris Hotel Denpasar is done using the Blackbox Testing Method. The result of this study is a web-based asset inventory information system that handles the company's asset management process at Harris Hotel Denpasar which consist of features such as the data additions, data updates, eliminating/reducting the asset request, recording of the damaged goods, recording of the activity log, printing reports into the spreadsheet and being able to display the asset of each department statistically.